Role of trust towards charity foundations in the relationship between emotional intelligence and psychological well-being in mothers of autistic children - Md Jani, Syahrina Hayati; Salleh, Nurjannah; Abdul Rasool, Mohamed Saladin; Mat Isa, Nurul Amyra (2023)
Philanthropic pursuits have become common nowadays as more people are motivated by a desire to contribute to the inclination and promotion of well-being and welfare of others, especially autism community. A charity foundation is believed to be one of the tools available to assist people in pursuing their charitable purpose. The present study aims to investigate the role of trust toward charity foundations in the relationship between emotional intelligence and psychological well-being in mothers of autistic children. This study used quantitative approach to answer the research questions. The research subject involved 105 mothers with autistic children. Mothers in this study have tremendous trust in charity foundations, and emotional intelligence has significant impacts on their trust. However, the result indicated that trust mediate the negative relationship between emotional intelligence and psychological well-being. Despite their trust in charity foundations, mothers believe that they need to reduce their trust in these institutions to have a better ability to manage their emotions, understand the emotions of those around them, and have a healthier state of psychological well-being. The study includes a sample that is limited to perceptions of mothers with autistic children and lacks representation from individuals living in rural areas. The constraints may have had an impact on the results, prompting additional study to duplicate and validate the findings. Prior research has found a relationship between emotional intelligence and psychological well-being. In addition, expected trust towards charity foundations able help to improve the psychological well-being of parents with autistic children, in most cases are mothers. As a result, it is critical to evaluate the trust established by mothers in charity foundations as a variable that influences the formation of ASD development. This result contradicts earlier studies while contributing new findings to the field of study.